Whey protein concentrate as a novel source of bifunctional peptides with Angiotensin-I converting enzyme inhibitory and antioxidant properties: RSM study - Abdelhameed Hussein, Fatima; Chay, Shyan Yea; Zarei, Mohammad; Muhammad Auwal, Shehu; Abdul Hamid, Azizah; Wan Ibadullah, Wan Zunairah; Saari, Nazamid (Multidisciplinary Digital Publishing Institute, 2020)
Whey protein concentrate (WPC) is a unique source of protein with numerous nutritional and functional values due to the high content of branched-chain amino acid. This study was designed to establish the optimum conditions for Alcalase-hydrolysis of WPC to produce protein hydrolysates with dual biofunctionalities of angiotensin-I converting enzyme (ACE) inhibitory and antioxidant activities via response surface methodology (RSM). The results showed that the optimum conditions were achieved at temperature = 58.2 °C, E/S ratio = 2.5%, pH = 7.5 and hydrolysis time = 361.8 min in order to obtain the maximum DH (89.2%), ACE-inhibition (98.4%), DPPH• radical scavenging activity (50.1%) and ferrous ion chelation (73.1%). The well-fitted experimental data to predicted data further validates the regression model adequacy. Current study demonstrates the potential of WPC to generate bifunctional hydrolysates with ACE inhibition and antioxidant activity. This finding fosters the use of WPC hydrolysate as a novel, natural ingredient for the development of functional food products.